Insects and spiders - Caputo, Christine A., 1966- (New York : Scholastic, 2012)
Learn about insects and spiders while building your science vocabulary. Includes vocabulary quizzes and answer key.
Irresistible insects -- Itsy-bitsy spider -- Crawling all around.
"20 science vocabulary words in every book!"--Cover.
"This edition is available for distribution only through the school market"--P. [4] of cover.
Includes index.
Keywords: Insects -- Juvenile literature; Spiders -- Juvenile literature